Application of 3D‐printed Customized Guides in Subtalar Joint Arthrodesis - Xiao‐jun Duan; Hua‐quan Fan; Fu‐you Wang; Peng He; Liu Yang (Orthopaedic Surgery, 2019)
Objective To explore the feasibility of 3D printed customized guides assisting the precise drilling of Kirschner wires in subtalar joint arthrodesis. Methods We retrospectively reviewed the data of 29 patients (30 subtalar joints) who underwent subtalar joint arthrodesis between 1 July 2013 and 31 December 2017. The customized guides were designed on a full‐scale 3D polylactic acid model made from computed tomography (CT) data of patients by Model Intestinal Microflora in Computer Simulation (MIMICS) software, which were manufactured by 3D printing technology. A total of 14 joints used customized guides (experimental group); the remained 16 joints used the traditional method (control group). The time of drilling the Kirschner wires to the correct position, the time of subtalar fusion, American Orthopaedic Foot & Ankle Society (AOFAS) scores, and complications were evaluated in both groups. Results All customized guides were successfully manufactured. In the experimental group, it took 2.1 ± 0.7 min to drill the Kirschner wire to the satisfactory position, and 2 cases needed to be re‐drilled; in the control group, it took 4.6 ± 1.9 min to drill the Kirschner wire to the satisfactory position (P < 0.05), and 8 cases needed to be re‐drilled. No serious complications occurred in both groups during and after the surgery. Postoperative radiographic fusion was confirmed in all cases. No significant difference was observed in the fusion time and AOFAS scores 1 year postoperatively between the two groups (P > 0.05). Conclusion It is safe to apply 3D‐printed customized guides for subtalar joint arthrodesis, which can assist the accurate drilling of Kirschner wires into the appropriate position according to the preoperative plan, and reduce the operation time as well as intraoperative radiation.